Modelling Flexible Human Resource Allocation by Stochastic Graph Transformation - Donyina, Adwoa; Heckel, Reiko (Electronic Communications of the EASST, 2011)
In order for business process models to accurately capture the flexibility of human actors, we have to allow for flexible task management and role allocation. That means to take into account deadlines and escalation procedures, consider access rights, but allow temporary promotion and dynamic assignment of actors. In order to meet these requirements we will represent the configurations of a business process as graphs and operations changing these configurations by graph transformation rules. We will propose a domain-specific notation to visualise rules and configurations. To analyse performance and reliability properties of such models, we use stochastic simulation. The approach is illustrated by means of a pharmacy case study.